2014
DOI: 10.1371/journal.pone.0086461
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Use of Dried Blood Spots for Monitoring HIV Viral Load and for Early Infant Diagnosis

Abstract: BackgroundDried blood spots (DBS) have been used as alternative specimens to plasma to increase access to HIV viral load (VL) monitoring and early infant diagnosis (EID) in remote settings. We systematically reviewed evidence on the performance of DBS compared to plasma for VL monitoring and EID.Methods and FindingsThirteen peer reviewed HIV VL publications and five HIV EID papers were included. Depending on the technology and the viral load distribution in the study population, the percentage of DBS samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
95
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 35 publications
11
95
2
Order By: Relevance
“…Furthermore, the large number of virus load tests that will be necessary to support the UNAIDS goals will likely require the use of a variety of testing strategies, including monitoring suppression through centralized testing of dried blood spots (DBS). The DBS approach allows increased accessibility of virus load testing in remote, lowresource settings, as DBS are simple and inexpensive to both collect and transport (28). Moreover, modeling data suggest that virus load monitoring using DBS provides a mechanism for the cost-effective delivery of ART in low-resource settings (29).…”
Section: Nfection With Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%
“…Furthermore, the large number of virus load tests that will be necessary to support the UNAIDS goals will likely require the use of a variety of testing strategies, including monitoring suppression through centralized testing of dried blood spots (DBS). The DBS approach allows increased accessibility of virus load testing in remote, lowresource settings, as DBS are simple and inexpensive to both collect and transport (28). Moreover, modeling data suggest that virus load monitoring using DBS provides a mechanism for the cost-effective delivery of ART in low-resource settings (29).…”
Section: Nfection With Human Immunodeficiency Virus Type 1 (Hiv-1)mentioning
confidence: 99%
“…Technological advances have supported this shift. For example, the reach of centralized laboratory testing can be extended through the use of specimen collection and stabilization technologies in combination with sample transport systems; such as the use of dried blood spots for HIV levels, malaria parasite detection and serology [6][7][8] . In addition, new portable and integrated technologies can allow testing at primary health facilities, providing greater access to care and adoption 9 .…”
mentioning
confidence: 99%
“…[14][15][16] Many studies have demonstrated that dried blood spots (DBS) are useful for infant HIV diagnosis and monitoring plasma HIV viral loads with an excellent analytical performance. [17][18][19] However, no data is available for a DBS testing pooling strategy to diagnose acute and early adult HIV infections. In this study, we investigated whether pooled dried blood spot (DBS) testing might be a feasible method to identify acute HIV infection in a moderate risk HVCT setting.…”
Section: Introductionmentioning
confidence: 99%